The Role of School Physical Education in Achieving Pupils’ Mental Health - Yamina BELGHOUL (Langues & Cultures)
This study aims to explore the meaning of physical education and the major concepts tackled by scholars and thinkers, its aspects, its objectives in the Algerian schools, and its role in achieving the pupils’ psychological health. The study reveals that physical education is crucial for the acquisition of physical abilities, namely: speed, flexibility, endurance, and muscular strength, in order to maintain physical fitness and health, as well as physical and mental abilities. Physical education teaches pupils to become responsible when doing tasks and also in their social relationships. It contributes in promoting sportsmanship between them, respecting rules and instructions, and more importantly, respecting each another, and accepting defeat. Moreover, we conclude that physical education in Algeria has objectives that must be fulfilled in order to align with the necessary requirements of the pupils, preparing them physically and psychologically to participate in various future sports and Olympic competitions and to honor their country.